+0  
 
+2
41
1
avatar+100 

The entire graph of the function f(x) is shown below (f is only defined when x is between -4 and 4 inclusive). How many values of x satisfy f(f(x)) = 2?

MIRB16  Aug 1, 2017
edited by Guest  Aug 1, 2017

Best Answer 

 #1
avatar+4155 
+1

Note that the coordinates are stated this way:  ( x, f(x) )

 

First, let's find what  x  values cause  f(x)  to equal  2  .

 

There is the point (-3, 2).     So...     f( -3 )  =  2

There is the point ( 0, 2).     So...     f(  0 )  =  2

There is the point ( 3, 2).     So...     f(  3 )  =  2

 

 

Now we want to know what  x  values cause f(x)  to equal  -3, 0, and 3  .

 

There are no points where f(x) = -3  .

There is the point (-4, 0).     So...     f( -4 )  =  0

There is the point (-2, 3).     So...     f( -2 )  =  3

 

So...now we know that..

 

    f( f(-4) )             Since  f(-4)  =  0  , we can replace  " f(-4) "  with  " 0 " .

=  f(   0   )              Since  f(0)   =  2  , we can replace  " f(0)  "  with  " 2 " .

=  2

 

    f( f(-2) )             Since  f(-2)  =  3 ,  we can replace  " f(-2) "  with  " 3 ".

=  f(   3   )              Since  f(3)   =  2  , we can replace  " f(3)  "  with  " 2 " .

=  2

 

There are two  x  values that satisfy  f( f(x) ) = 2  . They are:  x = -4  and  x = -2

hectictar  Aug 2, 2017
edited by hectictar  Aug 2, 2017
Sort: 

1+0 Answers

 #1
avatar+4155 
+1
Best Answer

Note that the coordinates are stated this way:  ( x, f(x) )

 

First, let's find what  x  values cause  f(x)  to equal  2  .

 

There is the point (-3, 2).     So...     f( -3 )  =  2

There is the point ( 0, 2).     So...     f(  0 )  =  2

There is the point ( 3, 2).     So...     f(  3 )  =  2

 

 

Now we want to know what  x  values cause f(x)  to equal  -3, 0, and 3  .

 

There are no points where f(x) = -3  .

There is the point (-4, 0).     So...     f( -4 )  =  0

There is the point (-2, 3).     So...     f( -2 )  =  3

 

So...now we know that..

 

    f( f(-4) )             Since  f(-4)  =  0  , we can replace  " f(-4) "  with  " 0 " .

=  f(   0   )              Since  f(0)   =  2  , we can replace  " f(0)  "  with  " 2 " .

=  2

 

    f( f(-2) )             Since  f(-2)  =  3 ,  we can replace  " f(-2) "  with  " 3 ".

=  f(   3   )              Since  f(3)   =  2  , we can replace  " f(3)  "  with  " 2 " .

=  2

 

There are two  x  values that satisfy  f( f(x) ) = 2  . They are:  x = -4  and  x = -2

hectictar  Aug 2, 2017
edited by hectictar  Aug 2, 2017

5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details